Penerapan SIA aplikasi IT Zein Akunting dalam bisnis UMKM pengusaha muslim se-Jawa Tengah - Sri Dewi Wahyundaru (Fakultas Ekonomi dan Bisnis Universitas Islam Nahdlatul Ulama Jepara, 2022)
The Badan Pusat Statistik in 2019 noted that Indonesia's population reached 268.5 million consisting of 181.35 million people of productive age. This shows that Indonesia has very high human resources. However, the number of human resources is not commensurate with the availability of job opportunities, especially with the occurrence of the Covid-19 pandemic at the beginning of 2020 which has an impact on all sectors of people's lives. In this pandemic era, many young people are entrepreneurs of MSMEs. Many challenges must be faced, both internally and externally, one of which is knowledge of the application of Accounting Information Systems. Zein Accounting was created to meet the need for accounting information that is relevant, reliable, complete, timely, easy to understand, and verifiable. The Zein Accounting application also has a very important role in assisting decision making in the management of small businesses for service or trade MSMEs. The results of the research test show that the accounting information system variable has a value of tcount < ttable where 0.583 < 1.676 with a significance level of 0.000 <0.05 so it can be stated that the accounting information system has a significant effect on the performance of MSMEs. Then, it is also shown that the variable of using accounting information has a positive and significant effect on the success of MSEs in Muslim entrepreneurs throughout Central Java. This means that increasing the use of accounting information in the business activities carried out will increase the success of MSMEs..